Types, Naming, Methods of Obtaining and Chemical Properties of Carbonic Acids - Gulaysha, Ashikbaeva; Bazarbay, Tanirbergenov (European Journal of Life Safety and Stability (2660-9630), 2023)
This article will talk about the types, naming, methods of obtaining and chemical properties of carbonic acids. Reasoned opinion and reasoning were used throughout the article. At the end of the article, conclusions and suggestions are presented.